2007
DOI: 10.1108/09544780710817900
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors of continuous improvement in the public sector

Abstract: Purpose-To determine the critical success factors (CSFs) for continuous improvement projects in the public sector. Design/methodology/approach-Theoretical paper based on a literature review. Findings-It would appear that there are factors that are important in manufacturing organisations that do not figure in service/public sector organisations and vice versa. Research limitations/implications-As few papers were identified, further research must be carried out into the CSFs to see if the differences between ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 51 publications
7
159
1
14
Order By: Relevance
“…All the studies found were concentrated on the manufacturing industry or the service industry in the private sector (Saraph, Benson & Schroeder 1989, Ahire & Golhar 1996, Flynn, Schroeder & Sakakibara 1994, Yusof & Aspinwall 1999, Bullington et al 2002, and Karuppusami & Gandhinathan 2006. The exception was a study by Fryer, Antony and Douglas (2007) who cite only four papers that researched the health service among the 29 papers they examined.…”
Section: Few Studies On Critical Success Factors Within the Public Sementioning
confidence: 99%
See 3 more Smart Citations
“…All the studies found were concentrated on the manufacturing industry or the service industry in the private sector (Saraph, Benson & Schroeder 1989, Ahire & Golhar 1996, Flynn, Schroeder & Sakakibara 1994, Yusof & Aspinwall 1999, Bullington et al 2002, and Karuppusami & Gandhinathan 2006. The exception was a study by Fryer, Antony and Douglas (2007) who cite only four papers that researched the health service among the 29 papers they examined.…”
Section: Few Studies On Critical Success Factors Within the Public Sementioning
confidence: 99%
“…As mentioned, many studies into the identification of critical success factors have been conducted mainly in the manufacturing industry and some specific areas of the service industry (Fryer, Antony & Douglas 2007). However, there were not too many studies into the public sector and none into internal IT services within the public sector.…”
Section: The Research Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Fryer et al (2007), the importance of TQM practices for implementation is to increase the success rate, reduce delivery time, and prevent disillusioned state with continuous improvement programs. However, SME owner-managers need to bear in mind that the success of TQM practice depends among other on the following:…”
Section: Total Quality Management: the Cost And Success Of Its Practimentioning
confidence: 99%